THE EFFECTIVENESS OF DESCRIBE AND DRAW TECHNIQUE TO IMPROVE STUDENT'S WRITING SKILL - Dede Khoirunisa; Juwita Boneka Sinaga (CAHAYA PENDIDIKAN, 2019)
ABSTRACTThe objective of the study is to find out whether Describe and Draw Technique is Effective or not in improving student ability in writing at SMKS Al-Jabar Batam this study is limited on Writing for Eleventh grade student at SMKS Al-Jabar Batam in Academic year 2018/2019.The study designed used by the researcher is quasi experimental design (pre-test and post-test control group). The population of study is eleventh grade students of SMKS Al-Jabar Batam. They are four classes of eleventh grade student with the total number 71 students. The samples of the study are two classes which consist of 24 student in experiment class and 24 students in control class. The instrument in this study is writing test. The data analyzed in using t-test.  According to the result of statistical calculation. The result showed that sig (2 tailed) of student pre-test and post-test in experimental was 0.401 and standard significant level it was 0.05 by comparing the sig (2 tailed) and standard significant level, it was known that sig (s2 tailed0 was bigger than standard significant. The calculation of testing hypothesis used T-test formula with Null Hypothesis (Ho) and Alternative Hypothesis (Ha) it can be sum up that tcount (1.729) ≥ ttable (1.71714). Therefore, Ho is rejected and Ha is accepted. The conclusion was Describe and Draw Technique gives significant effect in improving student ability in Writing. Keywords: Writing, improving, Describe and Draw Technique